PSEUDO MV-ALGEBRAS SI PSEUDO BL-ALGEBRAS - Constantin BOGDAN; Olimpia-Mioara PECINGINA (Fiabilitate şi Durabilitate)
This material is studying MV-algebras and BL-algebras in terms of applicability in Boolealgebra.Boole algebras expanded use in fuzzy logic.